Defect‐enhanced F– ion conductivity in layer‐structured nanocrystalline BaSnF4 prepared by high‐energy ball milling combined with soft annealing. Issue 1 (20th November 2014) - Preishuber‐Pflügl, Florian; Epp, Viktor; Nakhal, Suliman; Lerch, Martin; Wilkening, Martin
Abstract Fast ion conductors play one of the most important roles in solid state ionics as there is a great demand for their application in safe and powerful electrochemical energy storage systems. For such materials, it is known that the synthesis conditions may have significant impact on the final properties of the materials prepared. In this contribution, we made use of mechanosynthesis, carried out via high‐energy ball milling, to influence the ionic transport parameters of tetragonal, i.e., layer‐structured, BaSnF4. X‐ray powder diffraction (XRD) revealed that mechanical treatment of the binary fluorides BaF2 and SnF2 leads to a powder pointing to a nanocrystalline fluoride with (distorted) cubic symmetry. Differential scanning calorimetry (DSC) as well as preliminary in situ XRD measurements were used to follow the transformation towards the tetragonal modification with the composition BaSnF4. Broadband impedance spectroscopy was used to measure the overall electrical conductivity of the ternary fluoride. Remarkably, the layered form shows a room temperature conductivity of 7 × 10–4 S cm–1. Further emphasis was put on the characterization of the dielectric properties of the material, which was investigated by using different electrode materials to distinguish artefacts from intrinsic properties. Since we found a strong dependence of the real part of the permittivity on the electrode materials applied (carbon paste or sputtered Pt), we tend to assign the huge increase in permittivity, which was recently interpreted as giant dielectric constant, to interfacial polarization effects rather than to intrinsic properties. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)